Planning for the future of Masmoudi’s business family - Masmoudi, Mohamed (2018)
The following work project has the purpose of advising the Masmoudi family to plan for the future. The family and business were presented, the current situation of family governance was assessed, and the need for developing a family constitution was identified. For the purpose of developing such document, qualitative data from the members of the family was collected and analyzed, to eventually present a draft of the constitution. In the process, the concepts referred to in the literature review regarding family business and family business governance, were demonstrated in the discussions with the Masmoudi’s family members.